The unusual metal clusters of nitrogenase: structural features revealed by x-ray anomalous diffraction studies of the MoFe protein from Clostridium pasteurianum. - Bolin, J T (1993)
Nitrogenase (EC 1.18.6.1) catalyzes the conversion of dinitrogen to ammonia, the central reaction of biological nitrogen fixation. X-ray anomalous diffraction data were analyzed to probe the structures of the metal clusters bound by nitrogenase MoFe protein. In addition to one FeMo cofactor, each half-molecule of MoFe protein binds one large FeS cluster of a type not previously observed in a protein. The FeS cluster contains roughly eight Fe atoms, comprises two subclusters, and is separated from the FeMo cofactor by an edge-to-edge distance of 14 A. The inorganic framework of the FeMo cofactor is not resolved into subclusters, but the Mo atom is located at its periphery. FeMo cofactors in different half-molecules are 70 A apart and cannot promote binuclear activation of dinitrogen by two Mo atoms.